INTEGRASI ILMU KALAM, FIKIH, DAN TASAWUF DALAM PEMIKIRAN AL-GHAZALI: MEMBANGUN ISLAM YANG RASIONAL DAN SPIRITUAL - Mila Maulida Barrotuzzahro; Agus Khunaifi (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
Al-Ghazali is a central figure in the history of Islamic thought who successfully integrated the three main branches of Islamic sciences—kalam (theology), fiqh (jurisprudence), and tasawwuf (mysticism)—into a unified and harmonious epistemological framework. He viewed kalam not merely as a tool to defend Islamic creed against external threats, but also as a rational foundation for spiritual purification and ethical development. For Al-Ghazali, true Sufism must be firmly rooted in the Qur’an and Sunnah, while avoiding metaphysical and speculative deviations such as hulul (indwelling), ittihad (union), and emanative cosmology influenced by Neoplatonism. Through his monumental works like Ihya’ ‘Ulum al-Din and Minhaj al-‘Abidin, he demonstrated how the synthesis of disciplines could yield an understanding of Islam that is both rational and legalistic, yet deeply ethical and spiritual. Rejecting extreme forms of Sufism that neglect outward Sharia obligations, he emphasized a balanced path that unites knowledge and practice, aiming ultimately at ma‘rifah (gnosis) and true happiness (sa‘adah). His integrative vision not only provided a robust foundation for classical Islamic scholarship but also remains profoundly relevant to contemporary Islamic intellectual and spiritual discourse. This article systematically examines Al-Ghazali’s integrative thought, while addressing both critiques and appreciations of his position within the broader spectrum of Islamic sciences.